Analysis and implementation of a customer enterprise information system in the garment industry - Low, Poh Seng. (2008)
This report analyzes the design and implementation of Pacific Garment's enterprise web application. It also describes the design and implementation of a PDA (Personal Digital Assistant) based application that provides mobility to user to perform quotation computation. A spreadsheet is required in the calculation of the YY (Yardage Yield) document. The YY document is represented in the structured cells with trees as the logical data structures. A module to convert from in-order into post-order mathematical formula is required in order to represent the tree data structure. The PDA-based application is developed on the .NET compact framework (that runs on Windows CE) with C# as the primary programming language. The client/server architecture is used in the implementation instead of the web based approach. XML is used as the main data representation for the local file storage and data exchange over HTTP.